BUILDING THE STUDENTS' KNOWLEDGE OF THE FIELD: TEACHING READING DESCRIPTIVE TEXT FOR JUNIOR HIGH SCHOOL STUDENTS - Inka Rachmat, - (2019)
This study aims to investigate how the activities in building knowledge of the field help the students reading descriptive text. As a classroom action research, this study obtained the data by using three instruments namely classroom observation, interview, and students' works. This study involved seventh grade students in a Junior High School in Bandung as its participants. Using the activities adapted from Hammond's framework of BKOF (1992), Emilia's steps of BKOF (2011), and scaffolding theory as elaborated by Walqui (2006), this study found that the majority of the students were able to understand the descriptive text given. The findings indicated that the overall activities were helpful and enabled the students to understand the text more easily